Proteasome and p62/SQSTM1 are involved in methylmercury toxicity mitigation in mouse embryonic fibroblast cells - Nakamura, Ryosuke; Kiyono, Masako; Ohshiro, Yuka; Takanezawa, Yasukazu; Uraguchi, Shimpei (Journal of toxicological sciences, 2023)
Methylmercury (MeHg), an environmental pollutant, disrupts and impairs cellular function. MeHg binds to various cellular proteins, causing dysfunction and misfolding, which are considered underlying causes of MeHg toxicity. The p62 protein, also termed SQSTM1, is a ubiquitin-binding protein that targets ubiquitinated substrates to undergo autophagy and plays a key role in ameliorating MeHg toxicity. p62 also delivers ubiquitinated substrates to proteasomes. However, the role of these degradation systems in mitigating MeHg toxicity remains unknown. Herein, we explored the impact of the proteasome inhibitor MG132 on MeHg toxicity and examined the toxicity of co-treatment with MG132 and MeHg in p62KO mouse embryonic fibroblasts (MEFs) by analyzing cell viability, immunoblotting, mRNA levels, immunofluorescence, and the mercury content. The proteasome inhibitor MG132 enhanced MeHg-induced cytotoxicity while reducing intracellular mercury levels in MEFs. Co-treatment with MG132 and MeHg markedly increased levels of p62 and ubiquitinated proteins. Furthermore, co-treatment with MG132 and MeHg reduced p62KO MEF viability compared to that of wild-type MEFs. Our findings suggest that the proteasome participates in mitigating MeHg cytotoxicity, while p62 may play an important role in transporting MeHg-induced ubiquitinated proteins to the proteasome, as well as in autophagy. Collectively, these results imply that p62, and proteasome, and autophagy are vital for cytoprotection against MeHg toxicity.